2016
DOI: 10.14687/jhs.v13i3.3892
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and religious perspective of loss and bereavement in Anatolia

Abstract: Coping with death is a grueling job to be done however it is not impossible. All cultures have developed ways to cope with death. Interfering with these practices may interfere with the necessary grieving processes. Understanding different cultures' and religions response to death can help counselors recognize the grieving process in patients of other cultures. It is also important to realize that, while each individual grief process is unique, there is a form of grief that is disabling, interfering with funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This is mainly caused by the several caregiving responsibilities present, as well as a caregiver's family role. 30,[45][46][47] Given that primary caregivers, especially during end-of-life palliative care, have to deal with their caregiving workload while also managing the realization of an impending death, mental stress is greater than among primary caregivers of patients receiving active treatment. 1 The present study observed that anticipatory grief involves undergoing certain stages rather than remaining in a constant state of negative emotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly caused by the several caregiving responsibilities present, as well as a caregiver's family role. 30,[45][46][47] Given that primary caregivers, especially during end-of-life palliative care, have to deal with their caregiving workload while also managing the realization of an impending death, mental stress is greater than among primary caregivers of patients receiving active treatment. 1 The present study observed that anticipatory grief involves undergoing certain stages rather than remaining in a constant state of negative emotion.…”
Section: Discussionmentioning
confidence: 99%
“…The other most important requirements are that a dying person can utter Kelime-i Shahada, which can help them go to heaven eventually. 30 Cultural and religious practices applied while the individual is on his/her deathbed, during, and after his/her demise have a positive and soothing impact on the loved ones of the expired. Such practices as memorial service customs plan to add to the change, a transformation of the expired as well as those in grief.…”
Section: Domestic and International Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are expected to get to know and be closer to God. 26 The central point aims to implement death education since good and bad behavior lie in the soul and heart. 27 Although the cognitive-reason aspect also plays a significant role in assisting the implementation of death education, this cognitive-reason aspect functions as a medium for thinking, considering, guessing, assessing, and connecting with various phases or stages applied to death education.…”
Section: What Is Death Education Program?mentioning
confidence: 99%